p63/MT1-MMP axis is required for in situ to invasive transition in basal-like breast cancer - Lodillinsky, Catalina (2016)
The transition of ductal carcinoma in situ (DCIS) to invasive breast carcinoma requires tumor cells to cross the basement membrane (BM). However, mechanisms underlying BM transmigration are poorly understood. Here, we report that expression of membrane-type 1 (MT1)-matrix metalloproteinase (MMP), a key component of the BM invasion program, increases during breast cancer progression at the in situ to invasive breast carcinoma transition. In the intraductal xenograft model, MT1-MMP is required for BM transmigration of MCF10DCIS.com breast adenocarcinoma cells and is overexpressed in cell clusters overlying focal BM disruptions and at the invasive tumor front. Mirrored upregulation of p63 and MT1-MMP is observed at the edge of MCF10DCIS.com xenograft tumors and p63 is required for induction of MT1-MMP-dependent invasive program in response to microenvironmental signals. Immunohistochemistry and analysis of public database reveal that p63 and MT1-MMP are upregulated in human basal-like breast tumors suggesting that p63/MT1-MMP axis contributes to progression of basal-like breast cancers with elevated p63 and MT1-MMP levels.